Stimulation of Angiotensin Converting Enzyme 2: A Novel Treatment Strategy for Diabetic Nephropathy - Nomura, Haru; Kuruppu, Sanjaya; Rajapakse, Niwanthi W. (Frontiers in Physiology, 2022)
Despite current therapies for diabetic nephropathy, many patients continue to progress to end-stage renal disease requiring renal replacement therapy. While the precise mechanisms underlying diabetic nephropathy remain to be determined, it is well established that chronic activation of the renin angiotensin aldosterone system (RAAS) plays a substantial role in the pathogenesis of diabetic nephropathy. Angiotensin converting enzyme 2 (ACE2), the enzyme responsible for activating the reno-protective arm of the RAAS converts angiotensin (Ang) II into Ang 1-7 which exerts reno-protective effects. Chronic RAAS activation leads to kidney inflammation and fibrosis, and ultimately lead to end-stage kidney disease. Currently, angiotensin converting enzyme inhibitors and Ang II receptor blockers are approved for renal fibrosis and inflammation. Targeting the reno-protective arm of the RAAS should therefore, provide further treatment options for kidney fibrosis and inflammation. In this review, we examine how targeting the reno-protective arm of the RAAS can ameliorate kidney inflammation and fibrosis and rescue kidney function in diabetic nephropathy. We argue tissue ACE2 stimulation provides a unique and promising therapeutic approach for diabetic nephropathy.